1999
DOI: 10.1007/s003830050525
|View full text |Cite
|
Sign up to set email alerts
|

Pre-term and particularly pre-labor cesarean section to avoid complications of gastroschisis

Abstract: The marked advantages and merit of pre-term and particularly pre-labor (PTPL) cesarean section (C-section) in the avoidance, and indeed, virtual elimination of severely disabling gastroschisis (GS) complications in infants diagnosed prior to birth by ultrasound has unfortunately remained controversial in the 10 to 12 years since it was first reported and strongly recommended by numerous authors. During this period, GS has remained one of the four major causes of the short-gut syndrome (SGS) in infancy and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
2
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 17 publications
3
38
2
9
Order By: Relevance
“…It has been reported that uterine contraction and vaginal delivery can induce intestinal lesions and intestinal rupture [38]. On the other hand, CS may protect the bowel from dystocia, traumatism and microbial contamination [28,[39][40][41][42][43]. Recently, a meta-analysis by Segel et al [44] found that there was no significant relationship between mode of delivery and the rate of primary fascial repair, neonatal sepsis or paediatric mortality.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that uterine contraction and vaginal delivery can induce intestinal lesions and intestinal rupture [38]. On the other hand, CS may protect the bowel from dystocia, traumatism and microbial contamination [28,[39][40][41][42][43]. Recently, a meta-analysis by Segel et al [44] found that there was no significant relationship between mode of delivery and the rate of primary fascial repair, neonatal sepsis or paediatric mortality.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent randomised controlled trial of elective preterm delivery, Logghe et al [27] demonstrated that there was no significant benefit from this management. However, in 1999, Moore et al [28] proposed a preterm and particularly a prelabour CS to reduce peel formation and avoid complications of gastroschisis. Many authors [4][5][6][7] proposed that elective preterm delivery (before 35-38 weeks of gestation) using specific ultrasound criteria resulted in improved postoperative outcome without significant morbidity secondary to prematurity (pulmonary, digestive, neurological).…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que vários são os fatores pré-natais que poderiam influenciar na evolução clínica dos neonatos com gastrosquise, entre eles a idade materna (MOORE et al, 1999), a via de parto (MORETTI et al, 1990;DUNN et al, 1999), presença de estresse fetal (CRAWFORD et al, 1992). No caso dos dois MIRANDA, D.F.H.…”
Section: Discussionunclassified
“…6 In many instances at delivery no coagulum, oedema or indurations is present in the gut. 7 These features appear after birth, because of venous obstruction and transudation of proteinacious fluid. 8 Majority of babies with gastroschisis are born prematurely.…”
Section: Introductionmentioning
confidence: 99%